2015
DOI: 10.3928/00220124-20150619-04
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Practice Nursing Simulation for Neonatal Skill Competency: A Pilot Study for Successful Continuing Education

Abstract: This pilot study benefited advanced practice nurses by providing them with the potential to maintain competency in this high-risk, low-frequency procedure. Continuing education is an important consideration for health care organizations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 9 publications
0
9
0
1
Order By: Relevance
“…Research shows that healthcare providers’ skill retention declines as soon as three months after training [8, 9]. Factors known to affect skills and knowledge acquisition include motivation, the learning environment [10] and the use of simulation to enhance skills retention for low-frequency procedures [11]. Simulation-based mastery learning can improve medical students’ retention of core clinical skills and deliberate practice of clinical skills under the supervision of an engaged instructor is a key component of the mastery model [12].…”
Section: Discussionmentioning
confidence: 99%
“…Research shows that healthcare providers’ skill retention declines as soon as three months after training [8, 9]. Factors known to affect skills and knowledge acquisition include motivation, the learning environment [10] and the use of simulation to enhance skills retention for low-frequency procedures [11]. Simulation-based mastery learning can improve medical students’ retention of core clinical skills and deliberate practice of clinical skills under the supervision of an engaged instructor is a key component of the mastery model [12].…”
Section: Discussionmentioning
confidence: 99%
“…Factors known to affect skills and knowledge acquisition including motivation and learning environment [ 4 ], team leadership and communication [ 5 ], and use of simulators to enhance skills retention for low-frequency procedures [ 6 ] and others have been explored by various researchers. It has been shown that a strong health workforce leadership is an important factor to ensure motivation and create an enabling learning environment [ 7 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…attitude, eventually improving clinical based thinking competency and skills of nursing interns [4,9]. This study also revealed that CBL could improve critical thinking ability of students, suggesting that CBL-method in combined with casedirected study significantly improved core competency of nursing undergraduates in solving clinical problems, and made them more competent for clinical practice in future [5].…”
Section: Application Of Case-based Learning In Instructing Clinical Smentioning
confidence: 69%
“…Clinical practice is therefore one indispensable stage for nursing students transiting from class-based learning towards clinical practice. Teaching of nursing skills is the core syllabus of clinical intern [4,5]. However, the teaching of clinical skills still mainly depends on the teacher demonstration, followed by practice under supervision and evaluation, and largely ignoring cultivation of comprehensive analysis, communication, response and critical thinking features of students [6].…”
Section: Introductionmentioning
confidence: 99%